2018
DOI: 10.1128/microbiolspec.pfs-0021-2017
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexities of Food Safety Using a “One Health” Approach

Abstract: The philosophy of One Health is growing in concept and clarity. The interdependence of human, animal, and environmental health is the basis for the concept of One Health. One Health is a comprehensive approach to ensure the health of people, animals, and the environment through collaborative efforts. Preharvest food safety issues align with the grand concept of One Health. Imagine any food production system, and immediately, parallel images from One Health emerge: for example, transmission of zoonotic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…U.S. poultry processing incorporates scalding, washing, and chilling which are effective at reducing bacterial counts but do not eliminate all pathogenic bacteria from the finished meat products [7]. The animal carcass liquid film and skin crevasses provide a suitable microenvironment for Campylobacter survival during production [1,5]. Previous studies found Campylobacter contaminates approximately 50% of retail chicken meat in the U.S., and significantly less was found in other retail meat products [25].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…U.S. poultry processing incorporates scalding, washing, and chilling which are effective at reducing bacterial counts but do not eliminate all pathogenic bacteria from the finished meat products [7]. The animal carcass liquid film and skin crevasses provide a suitable microenvironment for Campylobacter survival during production [1,5]. Previous studies found Campylobacter contaminates approximately 50% of retail chicken meat in the U.S., and significantly less was found in other retail meat products [25].…”
Section: Plos Onementioning
confidence: 99%
“…Specifically, the consumption of poultry products are a known risk factor for human Campylobacter infections in the U.S and in other parts of the world. [1,[4][5][6]. Food animals (poultry, cattle and swine) are common asymptomatic reservoir hosts for pathogenic Campylobacter strains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feed is a paramount target for analysis since it situates at the start of the food chain and poor feed quality can affect the yield on food-producing animals [6]. Understanding the complexities of food safety is the goal of approaches such as One Health [7], Farm-to-Fork [6], or MyToolbox [8]. Furthermore, feed contaminants carryover downstream can reach products such as meat, eggs, and milk (see for example the transference of aflatoxin M 1 from aflatoxin B 1 -contaminated feed).…”
Section: Introductionmentioning
confidence: 99%